Caracterización del síndrome coronario agudo en adultos menores de 45 años de una institución especializada en la Habana, Cuba, entre 2013 y 2014 (2015)
ABSTRACT Introduction: Acute coronary syndrome in youngers than 45 years old constitutes a clinical condition with specific characteristics that tells it apart from older patients because the poor symptomatology previous to the origin of the acute coronary syndrome and the presence of peculiars risk factors such as connective tissue disorders, hypercoagulability states and the drugs intake, leads to lesser complications and better prognosis. Objective: characterize the acute coronary syndrome in young adults admitted at the Cardiology and Surgery Cardiovascular’s Institute between the years 2013 and 2014. Materials and Methods: Descriptive and transverse study with 99 patients under 45 years old who had acute coronary syndrome. There were analyzed clinical variables, diagnostic and therapeutic strategies. Results: The mean age was 42 years and the masculine sex was predominant. Smoking, arterial hypertension and dyslipidemia were the risk factors more common. The typical pain was in the 70.7% of patients. Electrocardiographic disorders of the inferior region (33.3%) and previous (22.2%) were the more frequents. The normal ejection fraction of the left ventricle (22.2%) predominated in the one vessel disease. The hypokinesia (48.5%) and akinesia (26.3%) predominated in this syndrome. The most responsible arteries were the descending previous (40.4%) and the right coronary (28.3%). The coronary percutaneous intervention was the procedure more made in acute coronary syndrome with ST segment elevation. Conclusions: The minimum extension of the coronary disease justified the conservation of the ventricular function, the segmentary hypokinesia and the softly percent of complications. The coronary percutaneous intervention constituted the strategy of re-perfusion more used in the acute coronary syndrome with elevation of the segment ST. MÉD UIS. 2015;28(3):281-90. Key words: Young adult. Acute coronary syndrome. Systolic volume. Segmentary motility. Percutaneous coronary intervention